Kekuatan Hukum Visum Et Repertum Sebagai Alat Bukti di Tinjau dari KUHAP dan Undang-Undang No.23 Tahun 2004 - Antory Royan Adyan (Universitas Bandar Lampung (UBL), 2010)
The basicly, humans is social beings who relating to others. However, relationshipswith others are not impossible will cause a problem, the problem is one of them isdomestic or family violence. It is criminal act, because it has violated the law. Theapproach used is the problem of the normative approach, it is reviewing regulations,book/ /literature and other scientific papers, empirical approach is performed as asupport for the completeness of normative data, data analysis in qualitative analysis.The result of this research has shown about strenght of Visum Et Repertum. Visum EtRepertum as complementary instrument to seacrhing for material truth, because thejudge is limited by certainly jugde principle and application of the minimun thresholdof authentucation, so that certainly jugde principle to became dominant faith.